STUDI KOMPARATIF PERKEBUNAN KELAPA SAWIT RAKYAT POLA PLASMA DAN POLA SWADAYA DALAM MENGHADAPI SERTIFIKASI RSPO - Ernia Lestari, Eka; Hutabarat, Sakti; Dewi, Novia (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2015)
Abstract In the last decade, there has been a spate of interest in how to reduce negative impacts of rapid oil palm plantation expansion caused by increasing demand for crude palm oil and fresh fruit bunches. Some international institutions proposed a certification program to ensure a sustainable oil palm production. However, certification become a huge challenge for oil palm smallholders. There are some barriers that the farmers face in accesing inputs, financial and marketing. The purpose of the present study was to analyse oil palm smallholders’ performance and challenges toward certification issues in palm oil supply chain. A survey was conducted to collect data in two types of smallholders, i.e. scheme and independent smallholders. The number of samples selected from the population is 150 samples consist of 70 independent smallholders’ samples and 80 scheme smallholders’ samples. The study assessed the existing performance of the smallholders plantation including farm income, oil palm productivity, and best practices in oil palm production. The study used household income analyses, comparative analyses, and assessment on the application of RSPO standards. The result shows that the performance of scheme smallholders are better than the Independent smallholders. There would be an increasing farm costs to comply with the RSPO standard. However, there would be no guarantte on premius price.